2019
DOI: 10.1007/s00170-019-03302-3
|View full text |Cite
|
Sign up to set email alerts
|

Weld process model for simulating metal active gas welding

Abstract: Generally, optimum welding variables and conditions of manufacturing are currently mainly determined by experiments for standardized production. Virtual manufacturing and virtual testing of weldments using finite element method provide a sustainable solution for advanced applications. The aim of the current research work is to develop a weld process model, using a threedimensional heat transfer model, to ensure general applicability for typical joints of stator segments of wind turbines as a final application.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…It is concluded that the best results are obtained when η = 85%; thus, this value is taken in the numerical calculations. A similar investigation of welding process efficiency based on the comparison of numerically and experimentally obtained data are presented by Kollár et al The transient temperature field from the thermal analysis because of the heat input, with the appropriate boundary conditions, is then applied as input thermal load for the subsequent mechanical analysis. The mechanical analysis is performed simultaneously in one step, without applying the element birth and death technique to cut down simulation time .…”
Section: Numerical Modelmentioning
confidence: 99%
“…It is concluded that the best results are obtained when η = 85%; thus, this value is taken in the numerical calculations. A similar investigation of welding process efficiency based on the comparison of numerically and experimentally obtained data are presented by Kollár et al The transient temperature field from the thermal analysis because of the heat input, with the appropriate boundary conditions, is then applied as input thermal load for the subsequent mechanical analysis. The mechanical analysis is performed simultaneously in one step, without applying the element birth and death technique to cut down simulation time .…”
Section: Numerical Modelmentioning
confidence: 99%
“…The thermal–mechanical simulation method acts as an effective approach to analyze the welding residual stresses (Fuina et al., 2019; Kollár et al., 2019). But the calibration of the model parameters remains a time‐consuming task, typically achieved by the trial and error method (Wang & Qian, 2022).…”
Section: Introductionmentioning
confidence: 99%